Composite material for molding profiling lining layer of latex glove by impregnation method and preparation method of composite material
By using composite materials of water, bacterial cellulose, quaternary ammonium salt and sodium alginate in latex gloves, the thin inner lining layer is formed by impregnation method, which solves the problem of insufficient finger perception and motion sensitivity caused by the fabric inner lining layer, and achieves the Higher perception and motion sensitivity and simplify process flow.
Patent Information
- Application Number
- CN202411651633.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The lining of existing latex gloves is usually fabric, which leads to reduced finger perception and motion sensitivity, and the process is cumbersome and the thickness improvement is limited, which cannot meet the needs of fine action occasions such as medical surgery.
Using a composite material composed of water, bacterial cellulose, quaternary ammonium salt and sodium alginate, a pronounced inner lining layer with a thickness of less than 20 μm on the hand mold by impregnation method, and using quaternary ammonium salt and glycerol to the bacterial cellulose The fiber surface modification improves the deformation ability of the inner lining layer and the bonding strength with the latex layer.
It realizes a thin and flexible inner lining, improves finger perception ability and motion sensitivity, reduces operator allergy risk, and simplifies the process flow, suitable for applications in fine action occasions such as medical surgery.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of latex gloves, and particularly relates to a composite material for a contoured lining layer of latex gloves formed by a dipping method and a preparation method thereof. Background Art
[0002] Latex gloves are a type of rubber gloves that are made of compounded rubber latex and are formed by dipping. As an individual hand protection equipment, rubber gloves are widely used in various industries of the national economy as well as in special occasions such as medical treatment and emergency rescue. Pure rubber gloves have shortcomings such as being difficult to wear with wet hands and weak tear / puncture resistance. Natural rubber may also cause allergic symptoms in users. In industry, a fabric lining structure is usually used to improve the wearability and tear / puncture resistance of rubber gloves. However, the seams formed by sewing the fabric lining will result in poor consistency between the shape of the lining and the shape of the hand. In addition, the fabric thickness limit of the fabric lining (usually cotton fabric) further reduces the operator's finger perception and movement sensitivity. Therefore, it is not suitable for use in some occasions such as medical surgery that require fine hand movements.
[0003] Cellulose is the most abundant natural polymer on earth and one of the most important biodegradable and renewable biomass resources. Cellulose-based materials have been successfully used in flexible wearable devices, LED displays, solar cell coatings, battery separators and other electronic devices due to their flexibility, bendability and low cost. Bacterial cellulose is a nano-sized fiber polymer synthesized by microorganisms (bacteria) through metabolism. Its unique fine nanoscale three-dimensional network structure gives it mechanical properties far superior to plant cellulose, making it a candidate material for the preparation of ultra-tough substrate films.
[0004] Latex gloves are formed by latex dipping using a hand mold (hand mould), and the usual process is hand mold cleaning - latex coagulant dipping and drying - latex dipping and drying - demoulding - post-processing. The existing glove lining layer is mostly fabric, such as the invention patent application with publication number CN113481735A, which discloses a radiation-proof rubber glove with lining, which specifically comprises first weaving a glove lining with a coated yarn containing silver fiber, putting the glove lining on the hand mold, heating the lining and dipping it with a coagulant; then dipping the hand mold frame with a rubber material containing barium sulfate or graphite and other radiation-resistant properties, pre-drying it to 40% to 70% dry; then dipping it twice, and then vulcanizing it to obtain the product. The invention uses a coated yarn obtained by coating silver fiber inside polyester / spandex / nylon yarn to weave a glove lining, and combines it with adding barium sulfate or graphite with radiation resistance to the rubber material to achieve radiation resistance. However, because the inner lining layer is still a fabric, the operator's finger perception and movement sensitivity are inevitably reduced during use. More importantly, this kind of glove with a fabric lining layer requires the fabric to be prepared first, and then the fabric is put on the hand mold for subsequent dipping operations. The process is relatively cumbersome, and the improvement in the thickness of the fabric is limited, which also leads to limited improvement in the finger perception and movement sensitivity of the resulting gloves when used. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a composite material for forming a contoured inner lining of latex gloves by dipping and a preparation method thereof. A hand mold with an inner lining coagulant on the surface is dipped into the composite material of the present invention and kept for 2 to 5 minutes. After being taken out, the inner lining can be directly formed on the hand mold. After being dried, the latex dipping of the latex gloves and other subsequent processes can be directly performed to obtain the latex gloves.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A composite material for a contoured inner lining layer of a latex glove formed by a dipping method, which is made of the following components in weight ratio:
[0008] Water 1000, bacterial cellulose 2-15, quaternary ammonium salt 0.1-4, sodium alginate 5-20, propylene glycol 2-10.
[0009] In the above-mentioned composite material formula, the bacterial cellulose can be provided in the form of a bacterial cellulose aqueous dispersion or in the form of a bacterial cellulose freeze-dried powder. When provided in the form of a bacterial cellulose aqueous dispersion, the product of the amount of the bacterial cellulose aqueous dispersion and its concentration is taken as the amount of bacterial cellulose, and the amount of water in the bacterial cellulose aqueous dispersion is also included in the range of the amount of water in the composite material formula.
[0010] In the formula of the above composite material, the quaternary ammonium salt is specifically a quaternary ammonium salt containing at least one linear long-chain alkyl group, alkyl ester group or aliphatic amide group with 12 to 18 carbon atoms in the molecular structure; preferably, it is a quaternary ammonium salt containing two linear long-chain alkyl groups with 12 to 18 carbon atoms and two methyl groups in the molecular structure; more preferably, it can be dioctadecyl dimethyl ammonium chloride, N-(2-hydroxy-3-lauryloxypropyl) dimethyl dodecyl ammonium chloride or lauroyl PG-trimethyl ammonium chloride.
[0011] In the formula of the composite material, the weight ratio of each component is: water 1000, bacterial cellulose 2.5-12, quaternary ammonium salt 0.1-3, sodium alginate 6-18, propylene glycol 3-8.
[0012] The method for preparing the composite material for forming the contoured inner lining of latex gloves by dipping method of the present invention comprises the following steps:
[0013] 1) Weigh each component according to the formula and set aside;
[0014] 2) placing water in a container, adding bacterial cellulose, stirring evenly, adjusting the pH of the system to 4.5-6.0, adding quaternary ammonium salt under ultrasound or ultrasound combined with stirring to modify the bacterial cellulose, and obtaining a surface-modified bacterial cellulose aqueous dispersion;
[0015] 3) Adding sodium alginate and glycerol to the obtained surface-modified bacterial cellulose aqueous dispersion, stirring to dissolve and then standing for a period of time to obtain the product.
[0016] In step 2) of the above method, the pH value of the system can be adjusted by using a proton donor that can ionize at least one hydrogen ion in an aqueous solution, such as potassium dihydrogen phosphate, hydrochloric acid, sulfuric acid or acetic acid.
[0017] In step 2) of the above method, in order to accelerate the dissolution of the quaternary ammonium salt so that it can participate in the modification of the bacterial cellulose as soon as possible, the system can be heated to 40-50°C before adding the quaternary ammonium salt after adjusting the pH value of the system. It is preferred to keep the temperature at this temperature until the added quaternary ammonium salt is completely dissolved. Under the action of ultrasound, the fiber network in the bacterial cellulose opens, and the dissolved quaternary ammonium salt is coated on the fiber surface, thereby realizing the modification of the bacterial cellulose by the quaternary ammonium salt. The time of the ultrasound or ultrasound combined with stirring is usually 4-8 hours. After the ultrasound or ultrasound combined with stirring is completed, it is necessary to stand for a period of time so that the bacterial cellulose network that is stretched and oriented by shear stress during stirring can be restored to the spatial distribution state (irregular, scattered spatial distribution) before the stress is subjected to Brownian motion, and the standing time is usually 12-24 hours.
[0018] In step 3) of the above method, from the perspective of accelerating the dissolution of sodium alginate and glycerol, it is preferred to heat the obtained surface-modified bacterial cellulose aqueous dispersion to 40-50°C before adding sodium alginate and glycerol, and stir at this temperature until the sodium alginate and glycerol are dissolved. After the dissolution is completed, it is also necessary to stand for a period of time so that the bacterial cellulose network stretched and oriented by shear stress during stirring can be restored to the spatial distribution state (random, scattered spatial distribution) before the stress is applied through Brownian motion. The standing time is usually 12-24 hours.
[0019] The operation of using the composite material of the present invention to dip-form the inner lining layer on the hand model is after completing the dipping and drying operation of the inner lining layer coagulant of the hand model. The inner lining layer coagulant used here is a conventional coagulant used in the dip-forming of existing latex gloves, such as a coagulant containing calcium ions. A reference coagulant formula is: 100 parts by weight of water, 20 parts by weight of calcium nitrate, 3 parts by weight of gelatinized starch, and 2 parts by weight of calcium stearate. During preparation, it is only necessary to mix the components evenly and let them stand for 10 to 24 hours, and stir them evenly before use.
[0020] After the inner lining is formed, the conventional processes in the production of latex gloves, such as latex coagulant dipping and drying, latex dipping and drying, are then carried out.
[0021] Compared with the prior art, the present invention is characterized in that:
[0022] 1. By utilizing the nanoscale and three-dimensional network structure of bacterial cellulose fibers, a latex glove contour lining layer with a thickness of less than 20 μm can be formed on a hand mold by a dipping method to solve the problem that the traditional lining layer is thick and has poor shape fit, which affects the flexibility of the operator's hand fine movements after wearing the gloves; at the same time, the lining layer can also block the migration of natural rubber protein between rubber and human skin to reduce the possibility of operator allergies.
[0023] 2. The surface of bacterial cellulose fibers is modified by quaternary ammonium salts and propylene glycol to regulate the interaction between bacterial cellulose fibers and improve their affinity with the latex layer, thereby increasing the deformation ability of the bacterial cellulose lining layer and its bonding strength with the latex layer.
[0024] 3. The thickness of the obtained lining layer can be adjusted by different bacterial cellulose contents and impregnation times in the composite material, which is simple and easy to operate.
[0025] 4. The composite material of the present invention can be directly integrated into the existing latex glove production line to make use of the existing latex glove production equipment and coagulant, thus saving fixed asset investment and production costs. DETAILED DESCRIPTION
[0026] The present invention is described in detail below in conjunction with embodiments, which are only used to explain the present invention rather than to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0027] Embodiment 1:
[0028] 1.1 Preparation of composite materials
[0029] (1) Formulation:
[0030] Deionized water 7520g, bacterial cellulose aqueous dispersion (Guilin Qihong Technology Co., Ltd., bacterial cellulose content of 0.8%) 2500g, dioctadecyl dimethyl ammonium chloride 4g, sodium alginate 50g, glycerol 20g.
[0031] (2) Preparation method:
[0032] Deionized water is first added into a container, and a bacterial cellulose aqueous dispersion is gradually added into the container under mechanical stirring and stirred evenly, and a 3 mol / L potassium dihydrogen phosphate aqueous solution is used to adjust the pH value to 5.0, and then the temperature of the system is raised to 50°C, and dioctadecyl dimethyl ammonium chloride is added under conditions of mechanical stirring and ultrasonic oscillation and stirred until completely dissolved, and then mechanical stirring and ultrasonic oscillation are continued in the container for 4 hours, and then the mixture is cooled to room temperature and allowed to stand at room temperature for 24 hours to obtain a surface-modified bacterial cellulose aqueous dispersion; the surface-modified bacterial cellulose aqueous dispersion is heated to 40°C, and glycerol and sodium alginate are added while mechanically stirring, and the mixture is continued to be stirred for 2 hours, and then cooled to room temperature and allowed to stand at room temperature for 12 hours to obtain a bacterial cellulose composite hydrosol, which is the composite material for the contoured inner lining layer of latex gloves formed by the dipping method of the present invention.
[0033] 1.2 Preparation of bacterial cellulose composite lining layer
[0034] 1.2.1 Cleaning of hand models
[0035] The hand mold is cleaned according to the commonly used industrial preparation method of latex gloves and is set aside for use after drying.
[0036] 1.2.2 Preparation of coagulant for bacterial cellulose composite lining layer
[0037] Use the coagulant commonly used in the latex glove industry for the inner lining of latex gloves. The specific coagulant formula is: 100 parts by weight of distilled water, 20 parts by weight of calcium nitrate, 3 parts by weight of gelatinized starch, and 2 parts by weight of calcium stearate. Mix the components evenly and let them stand for 12 hours before use.
[0038] 1.2.3 Preparation of bacterial cellulose composite lining layer
[0039] According to the conventional industrial preparation method of latex gloves, the temperature of the cleaned hand mold is adjusted to 45-65°C, and then the hand mold is slowly immersed in the coagulant described in the above 1.2.2. After keeping for 1-2 minutes, the hand mold is slowly taken out from the inner lining coagulant. The speed of immersion and removal can refer to the speed of immersing the hand mold in the coagulant and taking it out from the coagulant in the conventional industrial preparation method of latex gloves; the removed hand mold is dried by the conventional industrial preparation method of latex gloves to obtain a hand mold prepared with a coagulant layer for standby use.
[0040] According to the conventional industrial preparation method of latex gloves, the temperature of the hand mold prepared with a coagulant layer is adjusted to 45-65°C, and then the hand mold prepared with the coagulant layer is slowly immersed in the composite material prepared in the above 1.1. After keeping for 2-5 minutes, the hand mold is slowly taken out from the composite material. The speed of immersion and removal can refer to the speed of immersing the hand mold in latex and taking it out from latex in the commonly used industrial preparation method of latex gloves; the removed hand mold is dried using the commonly used industrial preparation method of latex gloves to obtain a hand mold with a contoured lining layer of a bacterial cellulose composite material prepared for standby use.
[0041] After the hand mold impregnated with the bacterial cellulose composite hydrosol layer is dried, the above operation can be repeated multiple times to obtain a bacterial cellulose composite material lining layer with a thickness that meets the expected requirements.
[0042] 1.3 Forming of latex gloves with bacterial cellulose composite lining
[0043] According to the conventional industrial preparation method of latex gloves, the temperature of the hand mold prepared with the bacterial cellulose composite material lining layer obtained in 1.2 above is adjusted to the process range, and then the latex coagulant is impregnated and dried, followed by post-treatment operations such as latex impregnation, drying and leaching, to obtain a latex glove with a bacterial cellulose composite material contoured lining layer.
[0044] Embodiment 2:
[0045] 1.1 Preparation of composite materials
[0046] (1) Formulation:
[0047] Deionized water 10000 g, bacterial cellulose freeze-dried powder (Beijing Guanlan Technology Co., Ltd.) 150 g, N-(2-hydroxy-3-lauryloxypropyl) dimethyl dodecyl ammonium chloride 7.5 g, sodium alginate 200 g, glycerol 100 g.
[0048] (2) Preparation method:
[0049] Deionized water is first added into a container, and bacterial cellulose freeze-dried powder is gradually added into the container under mechanical stirring and stirred evenly, and the pH value is adjusted to 4.5 with hydrochloric acid with a concentration of 2 mol / L, and then the temperature of the system is raised to 45°C, and N-(2-hydroxy-3-lauryl acyloxypropyl) dimethyl dodecyl ammonium chloride is added under the conditions of mechanical stirring and ultrasonic oscillation and stirred until completely dissolved, and then mechanical stirring and ultrasonic oscillation are continued for 8 hours in the container, and then cooled to room temperature and allowed to stand at room temperature for 24 hours to obtain a surface-modified bacterial cellulose aqueous dispersion; the surface-modified bacterial cellulose aqueous dispersion is heated to 40°C, glycerol and sodium alginate are added while mechanically stirring, and the stirring is continued for 8 hours, and then cooled to room temperature and allowed to stand at room temperature for 12 hours to obtain a bacterial cellulose composite hydrosol, which is the composite material for the contoured inner lining layer of latex gloves formed by the dipping method of the present invention.
[0050] 1.2 Preparation of bacterial cellulose composite lining layer
[0051] Same as Example 1.
[0052] 1.3 Forming of latex gloves with bacterial cellulose composite lining
[0053] Same as Example 1.
[0054] Example 3
[0055] 1.1 Preparation of composite materials
[0056] (1) Formulation:
[0057] Bacterial cellulose aqueous dispersion (Guilin Qihong Technology Co., Ltd., bacterial cellulose content of 0.8%) 10000 g, distilled water 80 g, lauroyl PG-trimethylammonium chloride 8 g, sodium alginate 100 g, glycerol 70 g.
[0058] (2) Preparation method:
[0059] Deionized water is first added into a container, and a bacterial cellulose aqueous dispersion is gradually added into the container under mechanical stirring and stirred evenly, and a 2 mol / L acetic acid aqueous solution is used to adjust the pH value to 4.0, and then the temperature of the system is raised to 40°C, and lauroyl PG-trimethylammonium chloride is added under conditions of mechanical stirring and ultrasonic oscillation and stirred until completely dissolved, and then mechanical stirring and ultrasonic oscillation are continued in the container for 6 hours, and then the mixture is cooled to room temperature and allowed to stand at room temperature for 20 hours to obtain a surface-modified bacterial cellulose aqueous dispersion; the surface-modified bacterial cellulose aqueous dispersion is heated to 50°C, and glycerol and sodium alginate are added while mechanically stirring, and the mixture is continued to be stirred for 6 hours, and then cooled to room temperature and allowed to stand at room temperature for 12 hours to obtain a bacterial cellulose composite hydrosol, which is the composite material for the contoured inner lining layer of latex gloves formed by the dipping method of the present invention.
[0060] 1.2 Preparation of bacterial cellulose composite lining layer
[0061] Same as Example 1.
[0062] 1.3 The molding of latex gloves with bacterial cellulose composite material lining layer is the same as that in Example 1.
Claims
1. A composite material for forming a contoured lining layer of latex gloves by dipping, characterized in that: It is made of the following components in weight ratio: Water 1000, bacterial cellulose 2-15, quaternary ammonium salt 0.1-4, sodium alginate 5-20, propylene glycol 2-10.
2. The composite material for the contoured lining layer of latex gloves formed by dipping method according to claim 1, characterized in that: The quaternary ammonium salt is a quaternary ammonium salt containing at least one linear long-chain alkyl group, alkyl ester group or aliphatic amide group with 12 to 18 carbon atoms in its molecular structure.
3. The composite material for the contoured inner lining of latex gloves formed by dipping method according to claim 1, characterized in that: The quaternary ammonium salt is a quaternary ammonium salt containing two linear long-chain alkyl groups with 12 to 18 carbon atoms and two methyl groups in the molecular structure.
4. The composite material for the contoured lining layer of latex gloves formed by dipping method according to claim 1, characterized in that: The quaternary ammonium salt is dioctadecyl dimethyl ammonium chloride, N-(2-hydroxy-3-lauryl acyloxypropyl) dimethyl dodecyl ammonium chloride or lauroyl PG-trimethyl ammonium chloride.
5. The composite material for the contoured lining layer of latex gloves formed by dipping method according to any one of claims 1 to 4, characterized in that: The weight ratio of each component is: Water 1000, bacterial cellulose 2.5-12, quaternary ammonium salt 0.1-3, sodium alginate 6-18, propylene glycol 3-8.
6. The method for preparing the composite material for the contoured lining layer of latex gloves formed by dipping method according to claim 1 comprises the following steps: 1) Weigh each component according to the formula and set aside; 2) placing water in a container, adding bacterial cellulose, stirring evenly, adjusting the pH of the system to 4.5-6.0, adding quaternary ammonium salt under ultrasound or ultrasound combined with stirring to modify the bacterial cellulose, and obtaining a surface-modified bacterial cellulose aqueous dispersion; 3) Adding sodium alginate and glycerol to the obtained surface-modified bacterial cellulose aqueous dispersion, stirring to dissolve and then standing for a period of time to obtain the product.
7. The preparation method according to claim 6, characterized in that: In step 2), after adjusting the pH value of the system, the system is heated to 40-50° C. and then quaternary ammonium salt is added to modify the bacterial cellulose.
8. The preparation method according to claim 6, characterized in that: In step 3), the obtained surface-modified bacterial cellulose aqueous dispersion is heated to 40-50° C., sodium alginate and glycerol are added, and stirred at this temperature until the sodium alginate and glycerol are dissolved.
9. The preparation method according to claim 6, characterized in that: In step 3), the standing time is 12 to 24 hours.
Citation Information
Patent Citations
Radiation-proof rubber gloves with lining and preparation method of radiation-proof rubber gloves
CN113481735A
Preparation method of antimicrobial bacterial cellulose material
CN105860121A
Long-cylinder chemical protective glove and treatment method for enhancing gripping force of long-cylinder chemical defense glove in oily environment
CN113861484A
Preparation method and application of bacterial cellulose / sodium alginate / SiO2 composite sponge material
CN116410513A
Method for drying bacterial cellulose and dried product
JP1997165402A